Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1200/jco.2015.33.3_suppl.526
|View full text |Cite
|
Sign up to set email alerts
|

Prediagnostic plasma adiponectin and survival among patients with colorectal cancer.

Abstract: Circulating adiponectin is inversely related to the risk of colorectal cancer (CRC). However, its influence on CRC survival is unclear. We conducted a prospective study to evaluate the association between prediagnostic plasma levels of adiponectin and mortality in patients with CRC. We identified 621 incident CRC cases who provided blood specimens prior to diagnosis within the Nurses' Health Study (NHS) and Health Professionals Follow-up Study (HPFS). Cox proportional hazards models were used to calculate haza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Moreover, a low postoperative/preoperative ADP ratio is recognized as a risk factor for postoperative infection in patients undergoing surgery due to gastric and CRC [12], and, therefore, some functional foods (soy genistein extract, lychee-derived low-molecular-weight polyphenol, olive extract, and turmeric) have been proposed to promote ADP secretion and thus inhibit cancer occurrence and recurrence [40]. On the other hand, prediagnostic low plasma ADP concentration is associated with increased CRC-specific and overall mortality [43], although Chun et al [30] suggest that dysregulation between high LEP and low ADP secretion (i.e., a low ADP-to-LEP ratio) is more important in colorectal carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a low postoperative/preoperative ADP ratio is recognized as a risk factor for postoperative infection in patients undergoing surgery due to gastric and CRC [12], and, therefore, some functional foods (soy genistein extract, lychee-derived low-molecular-weight polyphenol, olive extract, and turmeric) have been proposed to promote ADP secretion and thus inhibit cancer occurrence and recurrence [40]. On the other hand, prediagnostic low plasma ADP concentration is associated with increased CRC-specific and overall mortality [43], although Chun et al [30] suggest that dysregulation between high LEP and low ADP secretion (i.e., a low ADP-to-LEP ratio) is more important in colorectal carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Housa et al [138] found that compared with organ-confined prostate cancer, levels of circulating APN are higher in locally advanced cancer. More interestingly, circulating APN has been demonstrated to be positively correlated with the all-cause mortality rate in most clinical diseases, including breast cancer and colorectal cancer [139][140][141].…”
Section: Research Progress On Apn In the Peripheral Circulation And Tmentioning
confidence: 99%
“…Subsequently, however, the majority of studies have shown a positive association or no association of adiponectin with all-cause mortality and cardiovascular mortality [69]. These associations were described in a wide range of clinical conditions, in different genders and diverse ethnicities, and in the general population of older individuals [20,53,[104][105][106]; older patients with weight loss, low skeletal-muscle mass, and poor physical functioning [24]; elderly people with T2DM [107]; T2DM patients with acute coronary syndrome [21]; elderly men with chronic heart failure [104]; patients with chronic heart failure and cachexia [108]; myocardial infarction patients [109]; stable ischemic heart disease [110]; individuals with diabetes and recent acute coronary syndrome [21]; acute stroke patients [111]; peripheral artery diseases [112]; Japanese hemodialysis patients [113]; end-stage renal disease in patients with T1DM and T2DM [114]; cancer [115]; women with breast cancer [116]; and patients with colorectal cancer [117].…”
Section: Circulating Adiponectin Levels and Risk Of Deatharguments Famentioning
confidence: 99%